DAMPAK KONVERSI LAHAN SAWAH DI JAWA TERHADAP PRODUKSI BERAS DAN KEBIJAKAN PENGENDALIANNYA - IRAWAN, BAMBANG; FRIYATNO, SUPENA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 2, No. 2 Juli 2002)
The scarcity of land, especially sawah land is one of problems that cause to achieve rice production more difficult for producing the staple food. Because of that, the Indonesian status shifted from self sufficient to rice importer. The objective of this paper is to seek the size of sawah land conversion and how is the implication to the rice production, and how is the Government effort to control the sawah land conversion. By tabulation and simple mathematic approach, the result showed that during 18 years 26, 9 thousand hectares each year, occurred net sawah conversion in Java. During that period, net accumulation of rice losses was about 40, 6 million ton or 2, 2 million ton per year as an impact of sawah land conversion. The government effort to control sawah land conversion just conducted by law enforcement approach, which is still looking for the best way. So, the effectiveness of law enforcement to control sawah land conversion is still relatively low.
Keywords: Impact, Conversion, Production, Control.